Construction of "Moderate Codification" Legislative Model of Environmental Law - Ren, Weitong; Yang, Huaqiang (International Journal of Social Sciences and Public Administration, 2024)
At present, China’s environmental legal norms have presented a "point-like type", not forming a good branch legal structure system, many problems have been produced in the concrete application, this article through the analysis of a typical country’s environmental law codification mode, combining the present situation of our environmental rule of law, concluded that our country can be realized "the appropriate legal system", That is, the conclusion of the "double law source" mode of environmental law of "ecological environment code + single law". At present, China’s academic circles have reached a consensus on the "moderate codification" model for the codification of ecological environment code, but there are still differences on the understanding of the "moderate codification" theory. This paper holds that the "moderate codification" of ecological environment code includes the following two aspects: the moderation of the normative content and system, and the moderation of dynamic process. The following assumptions are made for the framework of China’s ecological environment code under the mode of "moderate codification" : adopting a "total-division" structure, including general provisions, pollution prevention and control, natural ecological protection, green and low-carbon development, and ecological environmental responsibility.